ANALISIS DAYA SAING EKONOMI KABUPATEN/KOTA DI PROVINSI LAMPUNG - Yulianita, Anna; Muflicha, Haqqie (Jurnal Ekonomi Pembangunan, 2023)
This study tries to use the calculation of economic competitiveness analysis which is seen from four indicators, namely the four indicators used to provide a score, namely consumption expenditure per capita, GRDP per capita, GRDP, and the level of employment opportunities in the regency/city of Lampung province using the Standard Deviation value approach. , then followed by analysis of panel regression data to see the effect of economic growth and the Human Growth Index on the value of the Economic Competitiveness Index in 16 regencies/cities of Lampung Province in 2015-2019. The results of the study show that from index calculations I compare the economy in the district/city of Lampung province for 5 years 16 districts/cities are always inconsistent except for the city of Lampung which has a rating of 1 with an average value of 20.77 in 2016-2019 and inversely proportional to the city metro. This research will further provide an economic analysis of how economic growth and the human development index affect the influence of economic competition, where the results of the analysis using the panel data regression method show that the model chosen by Fixed Effect Model (FEM) has an influence between HDI and the Economic Competitiveness Index with a probability of 0.002 in the negative direction while Economic Growth has no effect on the prob value of 0.377.